Trickery, mockery and the Scottish way of war - Macdonald, Alastair J (Proceedings of the Society of Antiquaries of Scotland, 2014)
Despite their prominence in later medieval Scottish narratives, the themes of trickery and mockery in the way war is presented have been subjected to little academic scrutiny. The current paper suggests that such scrutiny yields important insights. It is argued that trickery is given unusual weight in narrative sources to highlight Scottish ingenuity in defeating their more powerful English enemies in war. This is in turn reflective of actual Scottish military behaviour in which ruses of various sorts were practised, arguably more readily than in many other martial cultures. While this should not be taken to indicate that there was any significant Scottish departure from accepted ethics of war, it does highlight an element of distinctiveness both to the practice of war by the Scots and their martial self-perception. Mockery is often frequently deployed in sources depicting the Scots at war against the English. Often the intention is to subvert bombastic aristocratic attitudes, depicted as being typical of the English martial elite. This ties in with a representation of the Scots fighting a war that featured wide communal involvement and an earthier material culture. Again this is reflective of real reliance on a broad social spread participating in war, as necessitated by the realities of the Anglo-Scottish struggle and its significant imbalance of wealth and resources. By the time Hary's Wallace was composed, in the 1470s, suggestive shifts had taken place in how trickery and mockery in war were represented. There is in this text far less privileging of trickery, indicating a greater self-confidence among the Scots as the threat of English conquest became less sharp. Mockery has also changed in character, no longer seeking to puncture English aristocratic pretensions and instead offering a more generalised, and more brutal, attempt to highlight the complete moral depravity of the old enemy.